Strategi Pengembangan Wisata Pantai Batu Gong di Desa Batu Gong Kecamatan Lalonggasumeeto Kabupaten Konawe - Thayeb, Jusran; Alam Lawelle, Sjamsu; Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2021)
This study aims to determine the developing strategy of Batu Gong beach tourism in Batu Gong Village, Lalonggasumeeto District, Konawe Regency, which was carried out from October to November 2019. The selection of research locations was carried out purposively. The sampling technique used in this study used two methods, namely accidential sampling and purposive sampling. The data analysis used in this study is a SWOT analysis which aims to see the strengths, weaknesses, opportunities and threats. The results of the analysis show that the Batu Gong beach development strategy is (SO) utilizing locations that are easily accessible to tourists and adding facilities to attract people to visit, take advantage of the location. which stretches widely that can be used as employment opportunities so as to improve the economy of the local community, utilize social media technology and print media to introduce tourism objects, and take advantage of good relations with all stakeholders to improve the provision of facilities. (S-T) increases security to avoid criminal acts against tourists and takes advantage of the easy-to-reach location, available facilities as a tourist attraction's advantage over other tourist attraction competitors. (W-O) enhances relations through good cooperation with stakeholders related to beach cleanliness management, arrangement and supplies of gazebos and increasing promotional activities on social media and print media to introduce tourist objects. (W-T) improve beach cleanliness and control from the authorities to reduce the risk of brawls / fights and criminal acts.